2023
DOI: 10.3390/v15030641
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing Astragalus Polysaccharide PG2 for Inhibiting ACE2 and SARS-CoV-2 Spike Syncytial Formation and Anti-Inflammatory Effects

Abstract: The outbreak of coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) poses a serious threat to global public health. In an effort to develop novel anti-coronavirus therapeutics and achieve prophylactics, we used gene set enrichment analysis (GSEA) for drug screening and identified that Astragalus polysaccharide (PG2), a mixture of polysaccharides purified from Astragalus membranaceus, could effectively reverse COVID-19 signature genes. Further biological as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…The injection of PG2, suggested to possess properties that are anti-inflammatory, immune-regulating, and beneficial for hematopoiesis, has been reported to have a notable positive impact on both fatigue and quality of life. [ 51 , 52 ] It has been shown that PG2 helps to improve the neutrophil-to-lymphocyte ratio in lung cancer patients treated with immunotherapy. [ 53 ] All 3 RCTs examined patients with advanced cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The injection of PG2, suggested to possess properties that are anti-inflammatory, immune-regulating, and beneficial for hematopoiesis, has been reported to have a notable positive impact on both fatigue and quality of life. [ 51 , 52 ] It has been shown that PG2 helps to improve the neutrophil-to-lymphocyte ratio in lung cancer patients treated with immunotherapy. [ 53 ] All 3 RCTs examined patients with advanced cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, no research has discovered that the tonic Chinese herbal medicine polysaccharides can result in a cytokine storm, which may be connected to the advantages of Chinese medicine, including alleviating the effect, various targets, and overall regulation. The production of antiinflammatory cytokines and M2 macrophage polarization by PG2 have been demonstrated to be effective treatments for cytokine storms caused by COVID-19 lung injury [111].…”
Section: Safety Evaluation Of Tonic Chinese Herbal Medicine Polysacch...mentioning
confidence: 99%